Pengembangan Desain Kemasan Produk Makanan Khas Serang Kue Satu Kacang Hijau Model Standing Pouch Pada Umkm Yuli Jaya Kota Serang - Febriani, Reni; Suhendri, Babay; Baslayn, Dihan Ahmad (LPPM Universitas Banten jaya, 2024)
The Kue Satu of Yuli Jaya's is a tradisional food of Serang City. It has been produced for decades, for generations. Marketed not only in the city of Serang but also outside the City of Serang. Usually sent to several souvenir centers. The packaging is still simple, using transparent plastic and labeled, so simply. Recently, Kue Satu Yuli Jaya made packaging with a box model, made from art carton. However, this packaging model has the disadvantage of not being able to waterproof and also being unable to hold heavy objects. Especially if it is placed in a damp place the cake will become wet or 'sluggish' thereby reducing the delicacy of the food. This research will focus on developing a packaging design for Kue Satu, changing the packaging design to make it more attractive and able to increase sales. The formulation of this research are (1) Analysis of the current packaging of Kue Satu Yuli Jaya's, (2) How to develop the packaging design, and (3) How is the result of developing the packaging design for Kue Satu Yuli Jaya’s using a Standing Pouch. The method using R&D (Research and Development). This method is used to produce products and test the effectiveness of product functions. Packaging design development is presented in a visual form by including logos, typography, illustrations, product photos, colors and product information. The type of packaging used is a standing pouchfoil aluminum.